Financial inclusion in Nigeria : issues and challenges - Kama, U.; Central Bank of Nigeria, Research Department; Adigun, M. (Abuja, Nigeria Central Bank of Nigeria, 2013)
The paper reviewed experiences of other countries in the achievement of financial inclusion and past and present efforts at promoting financial inclusion in Nigeria.
Includes bibliographical references.
oif 16/05/17
Ref.
Keywords: Financial inclusion; Personal finance; Nigeria